RUGBY IN PHYSICAL EDUCATION: FROM TEACHER TRAINING TO INTERSCHOOL FESTIVALS - Eraldo dos Santos Pinheiro; Patrícia da Rosa Louzada da Silva; Camila Borges Müller; Ciana Alves Goicochea; Gustavo Dias Ferreira; Gabriel Gustavo Bergmann (Journal of Physical Education)
ABSTRACT The school is an important environment for the development of physical and sports activities. Thus, to deconstruct the polarization of school sport, rugby emerges as an alternative to Physical Education (PE) classes. This article aimed to describe the process of introducing rugby in the school environment in the city of Pelotas/RS. This case study originates from an extension project developed to introduce rugby in the Pelotas-RS schools. Between 2015 and 2017, 102 teachers participated in the project, reaching around 9,600 students in PE classes and 995 students in the festivals. In addition, most teachers showed an interest in the modality as an alternative of content and wanted to learn and reproduce it. Finally, rugby was introduced into the teaching plans and viewed positively as an alternative to PE classes.